Analysis of Gear Dynamic Characteristic of Oil Churning Resistance under Stochastic Disturbance - Wenyu Liu; Yongguo Sun; Guangbin Yu; Valerii Tupolev; Wei Liu (Jixie chuandong)
Oil churning lubrication is an important lubrication method of gear system. Considering the viscoelasticity of the lubricant oil will result in additional resistance upon gears immersed in the oil while running at high-speed，and the gear system can get disturbed at all times due to self-exciting vibration and other factors. Thus，considering the backlash，time-varying mesh stiffness，transmission error，stochastic disturbances，oil churning resistance and other nonlinear factors， compares and analyzes the influence of oil churning resistance upon dynamic characteristics of the gear system under stochastic disturbance by establishing a nonlinear dynamic model of straight gears with 6 degrees of freedom and using by Lagrange method using the bifurcation diagram，phase diagram，Poincarè diagram，time-history graph and dynamic load factors （DLF） obtained by the R-K method. The results show that stochastic disturbances can change the chaotic characteristics of the system，and its influence on the phase diagram is particularly obvious，the trajectory shape remains the same，but the periodicity is significantly affected and the periodic motion turns to quasi-periodic motion. When the condition of being under stochastic disturbances is considered as a normal working state，the oil churning resistance can make the system enter the chaotic state in advance.